Formulation and Performance Evaluation of Berberis Aristata Extract Loaded Ethosomal Gel (Asian Journal of Pharmaceutics (AJP), 2017)
Aims: The aim of the present research work is to prepare ethosome of standardized Berberis aristata extract and to evaluate for vesicle shape, size, polydispersity index (PDI), zeta potential (ZP), entrapment efficiency (EE), and in vitro permeation studies. Materials and Methods: Ethosomes were prepared using soyaphosphatidylcholine (1-3%) and ethanol (10-40%) by modified cold method and were characterized. Results: The size of ethosomes were found to be in the range of 110.98-357.34 nm while PDI ranges from 0.114 to 1.56 and ZP was between âˆ’20.0 and âˆ’39.4 mV. Morphology studies showed unilamellar structure under transmission electron microscope and phase contrast microscope showed smooth surface. The EE of ethosomes was found to be in the range of 48.05% to 92.08%. Ethosomes were further added to carbopol 934P for gel formation, and subsequently, evaluated for their physicochemical properties. Discussion: In vitro diffusion study was conducted for ethosomal dispersion, hydroethanolic solution, ethosomes incorporated in viscous gel, and conventional gel using Franz diffusion cell for the biomarker compound berberine. Conclusions: It can be concluded that B. aristata loaded ethosomal delivery system is an encouraging approach for herbal drugs.